2021
DOI: 10.1155/2021/9957490
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of 78 Compounds of Rhodiola rosea Extract by Supercritical CO2-Extraction and HPLC-ESI-MS/MS Spectrometry

Abstract: The plant Rhodiola rosea L. of family Crassulaceae was extracted using the supercritical CO2-extraction method. Several experimental conditions were investigated in the pressure range of 200–500 bar, with the used volume of cosolvent ethanol in the amount of 1% in the liquid phase at a temperature in the range of 31–70°C. The most effective extraction conditions are pressure 350 bar and temperature 60°C. The extracts were analyzed by HPLC with MS/MS identification. 78 target analytes were isolated from Rhodiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Nevertheless, it is important to note that the terpenoid family may participate substantially in the bioactivity demonstrated by blackberry fruits and extracts. Regarding terpenoids, the iridoid ebuloside (rt = 4.023 min) was identified previously on Sambucus ebulus [ 40 ], cinnamoside (rt = 5.189) in Cinnamomum cassia [ 41 ], rhodioloside A (rt = 6.117 min) in Rhodiola rosea [ 42 ], scutalpine F (rt = 9.811) in Scutelaria alpina [ 43 ] and tropeoside B1 (rt = 11.338 min) in Allium cepa [ 44 ]. Gradillas et al identified for the first time in blackberry leaves a family of terpenoids derived from ursolic acid which we have identified in blackberry fruits and which are the most abundant family of compounds present, being 93.4% of the total terpene content and the 88.8% of the total bioactive compounds quantified in the extract.…”
Section: Resultsmentioning
confidence: 97%
“…Nevertheless, it is important to note that the terpenoid family may participate substantially in the bioactivity demonstrated by blackberry fruits and extracts. Regarding terpenoids, the iridoid ebuloside (rt = 4.023 min) was identified previously on Sambucus ebulus [ 40 ], cinnamoside (rt = 5.189) in Cinnamomum cassia [ 41 ], rhodioloside A (rt = 6.117 min) in Rhodiola rosea [ 42 ], scutalpine F (rt = 9.811) in Scutelaria alpina [ 43 ] and tropeoside B1 (rt = 11.338 min) in Allium cepa [ 44 ]. Gradillas et al identified for the first time in blackberry leaves a family of terpenoids derived from ursolic acid which we have identified in blackberry fruits and which are the most abundant family of compounds present, being 93.4% of the total terpene content and the 88.8% of the total bioactive compounds quantified in the extract.…”
Section: Resultsmentioning
confidence: 97%
“…Mey [ 16 ]. Moreover, herbacetin 3- O -glucoside-8- O -xyloside was found in Rhodiola rosea L. [ 17 , 18 , 19 , 20 ]. In Sedum species, herbacetin 3- O -glucoside-8- O -xyloside was found in S. takesimense Nakai [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rhodiola rosea extract has been used as a dietary supplement to non-specifically enhance natural resistance to physical and behavioral stress, attenuating fatigue and depression [76] . Rhodiola rosea, whose roots are commonly used, contains phenylpropanoids (rosmarinic acid, rosin, and rosmarinic acid), phenolic compounds (rhodiol and p-tyrosol), flavonoids, and organic acids (gallic acid) [77] . Reports have demonstrated that it helps cope with various psychological and physical stresses by improving the body's ability to avoid injury and promoting adaptation to environmental stresses, including oxidative stress, anxiety, and physical exercise [78] (Table 3).…”
Section: Rhodiola Roseamentioning
confidence: 99%